Evaluation of PAI Learning Based on Character Education at SMA Al Islam 1 Surakarta - Aryeni Ika Febriyana; Hajar Sailirrohmah; Hanifia Rahma Praditasari; Nurul Latifatul Inayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Positive Islamic and traditional values are instilled in students in order to attain the goal of character education, which pertains to their spiritual formation and attitudes. If we examine more thoroughly, though, we can conclude that character education's primary objective has either failed or been unmet. This is evident in the contemporary globalization period. The sophistication of information technology is rising in the globalization period. However, there are drawbacks to technological advancement. A reduction in employee morale is one of them. It is evident from the aforementioned occurrence that educational institutions face a challenge in molding their students' Islamic personalities. As previously mentioned, the rise of undesirable things like marriage has made it necessary for youngsters to be taught morality and etiquette in line with religious principles. It is crucial that we use habituation techniques to instill Islamic character traits in our children. SMA Al-Islam Surakarta is among the educational institutions that employ the habituation method to instill Islamic character formation in their pupils. The purpose of this study is to investigate the application of the habituation approach to the development of Islamic character at SMA Al-Islam Surakarta, as well as the elements that facilitate the development of Islamic character in students enrolled in the school. to be aware. suppressing Islam and the values of the Al-Islam Surakarta High School pupils. Qualitative field research is what this study is. This study employed observation, interviews, and documentation techniques as its methodology.